2018
DOI: 10.1080/02770903.2018.1502301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic corticosteroids on blood eosinophil counts in asthma: real-world data

Abstract: Blood eosinophil counts decreased following initiation of SCS therapy and had not returned to index levels several weeks after SCS discontinuation. The time frame of SCS discontinuation is an important consideration when identifying patients with eosinophilic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 16 publications
0
33
1
4
Order By: Relevance
“…This would favour persistent type 2 disease expression despite high dose steroid therapy and contribute to persistent blood eosinophilia. Both of these proposed mechanisms reinforce the importance of interpreting eosinophil blood test results in the context of disease state, co‐morbidities and treatment being taken 43 and explain why a single cross‐sectional measure may be an imperfect biomarker for T2 high asthma 44 or anti‐IL5 therapy response 45 …”
Section: Discussionmentioning
confidence: 82%
“…This would favour persistent type 2 disease expression despite high dose steroid therapy and contribute to persistent blood eosinophilia. Both of these proposed mechanisms reinforce the importance of interpreting eosinophil blood test results in the context of disease state, co‐morbidities and treatment being taken 43 and explain why a single cross‐sectional measure may be an imperfect biomarker for T2 high asthma 44 or anti‐IL5 therapy response 45 …”
Section: Discussionmentioning
confidence: 82%
“…The non-availability of a specific drug to target the downstream pathways of Th2-driven mechanisms and their modulations by miRNAs restricts therapy in these conditions (21). The situation is also complicated by an overdependence on long acting corticosteroids, which has potential side effects (2224). We and others have shown that resveratrol is highly effective in suppressing inflammation in many autoimmune disease models (2527).…”
Section: Introductionmentioning
confidence: 99%
“…Зокрема, застосування глюкокортикоїдів, β 2 -агоністів, теофілінів та кромонів знижує кількість еозинофілів та їхніх продуктів у крові. Збільшення кількості еозинофільних гранулоцитів у периферичній крові переважно пояснюють міграцією клітин із шокових органів у кров по завершенню гострого періоду хвороби 15 .…”
Section: вступunclassified
“…P. 1040-1051. 15 Ortega H., Llanos J.P., Lafeuille M.H., et al Effects of systemic corticosteroids on blood eosinophil counts in asthma: real-world data. J Asthma.…”
Section: вступmentioning
confidence: 99%